Problematika Perlindungan Hukum Pemegang Polis Asuransi pada Kepailitan Perusahaan Asuransi: Analisis terhadap Undang-Undang Kepailitan dan Undang-Undang Asuransi: Penelitian - Elsa Gravionika; Amirah Dwi Subarkah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Insurance company bankruptcy raises complex problems related to the legal protection of policyholders as creditors with special characteristics. This study analyzes the legal position of policyholders and the claim settlement mechanism in the bankruptcy process of insurance companies according to Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU) and Law Number 2 of 1992 in conjunction with Law Number 40 of 2014 concerning Insurance. The research method used is normative juridical with a statutory and conceptual approach, using primary legal materials in the form of laws and court decisions, as well as secondary legal materials from related literature. The results of the study indicate that policyholders have a position as preferred creditors in bankruptcy based on Article 60 of the Insurance Law, but the existing protection mechanism still has weaknesses in its implementation, especially in terms of claim verification, limited assets, and coordination between institutions. This problem is exacerbated by the unclear technical implementation and the length of the claim settlement process, which is detrimental to policyholders. A more comprehensive regulatory reformulation, the establishment of a special guarantor institution, and the strengthening of the preventive supervision system are needed to ensure legal certainty and optimal protection for policyholders facing the risk of insurance company bankruptcy.